2019
DOI: 10.3221/igf-esis.51.17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between microscopic analysis and quantitative and qualitative indicators of moisture susceptibility evaluation of warm-mix asphalt mixtures containing modifiers

Abstract: Given the defects of bitumen in asphalt mixtures particularly exposed to moisture, this study mainly aims to investigate the relationship between qualitative and quantitative results of moisture susceptibility tests on asphalt mixtures modified by ZycoTherm, nanoclay, nanosilica and SBS. The Marshall stability, modulus of resilience and indirect tensile strength tests are carried out. Boiling water and SEM qualitative tests are also used. Eventually, the qualitative tests results are digitalized through image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The bitumen-polymer mixing phase is critical and largely determines the success of the mixing, for this purpose special attention must be paid during all modification phases. The temperature, time and speed of mixing were chosen based on previous studies established by the researchers [12,28,29,30,31]. Used equipment: -electric propeller agitator (rotation speed = 2000 rpm), -adjustable heating plate, -digital thermometer.…”
Section: Modification Processmentioning
confidence: 99%
“…The bitumen-polymer mixing phase is critical and largely determines the success of the mixing, for this purpose special attention must be paid during all modification phases. The temperature, time and speed of mixing were chosen based on previous studies established by the researchers [12,28,29,30,31]. Used equipment: -electric propeller agitator (rotation speed = 2000 rpm), -adjustable heating plate, -digital thermometer.…”
Section: Modification Processmentioning
confidence: 99%
“…Latex polymers increase stability by creating a hydrophobic effect or covering the pores [15]. In addition, pozzolanic additives, such as microsilica and nanosilica, act as micro fillers and cement adhesive additives, increase cement density, and reduce pores and permeability [16][17][18][19]. Regarding the effects of nanosilica and microsilica alone and in combination, researchers have shown that the combination of these two additives to the optimal amount in concrete samples increases the compressive strength of the samples in the short and long term.…”
Section: Introductionmentioning
confidence: 99%